Klasifikasi Data Karyawan Outsourcing Berdasarkan Penempatan Menggunakan Metode Naive Bayes Pada PT. Solusi Gemilang Persada - Fauzan Latief Mukmin; Yupianti Yupianti; Devi Sartika (Jurnal Media Infotama, 2024)
PT Solusi Gemilang Persada is one of the companies providing outsourced employee services in Bengkulu City. In this company, every 3 months a performance evaluation will be carried out on outsourced employees based on placement to determine whether the outsourced employee will have his contract extended or not. Classification of outsourced employee data based on placement using the Naive Bayes Method at PT. Solusi Gemilang Persada, can help facilitate the company in managing outsourced employee data and assessing the performance of outsourced employees and can help the company in providing recommendations for each outsourced employee whether the contract is extended or not extended based on the classification results. From the amount of test data used as much as 10 outsourced employee test data, the classification results show that the classification of the extended contract class is 8 (eight) outsourced employees, and the classification of the non-extended contract class is 2 (two) outsourced employees. Based on system tests that have been carried out, it can be concluded that the functional classification application of outsourced employee data based on placement using the naive bayes method at PT. Solusi Gemilang Persada has run well and is able to provide classification results for each outsourced employee performance assessment.